THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON PURCHASING DECISIONS WITH BRAND IMAGE AS MEDIATION IN BASEUS BRAND MOBILE PHONE ACCESSORIES PRODUCTS IN INDONESIA - Christian, Mario Alvin; Pardede, Ratlan (Ridwan Institute, 2024)
This study aims to analyze the influence of product price and product quality on purchase decisions, as well as the role of brand image as a mediating factor. The data was collected using a cross-sectional survey, where respondents were selected by purposive sampling from consumers of Baseus brand mobile phone accessories in various major cities in Indonesia. This study uses a quantitative method with a causal approach to examine the cause-and-effect relationship between price, product quality, and purchase decisions. The structural model and measurement model are then tested using the Partial Least Square (PLS) technique to test the hypothesis and feasibility of the model. The results of this study show that price has a significant influence on purchasing decisions, either directly or through brand image mediation. Moreover, the results of the study suggest that Baseus needs to consider product quality factors in the development of their brand image.